The Relationship between Knowledge, Attitudes, and Community Actions towards Preparedness for Earthquake and Tsunami Disasters in Tanjung Padang Village, Sirenja District, Donggala Regency - Tri Rizkiyanti Alwi; Sy. Rugaiyah; Sri Andriany Susilawati; Moh. Rifki; Zhanaz Tasya; Finta Amalinda (Journal of Public Health Indonesian, 2025)
This study aims to analyze the effect of outreach on changes in community knowledge, attitudes, and actions in facing earthquake and tsunami disasters. The method used is quantitative with a one-group pretest-posttest design. The sample consisted of 30 respondents from Tanjung Padang Village, Sirenja District, Donggala Regency, who were selected using purposive sampling. The data collection instrument was a questionnaire administered before and after the outreach. The results showed a significant increase in the average score of knowledge (from 55.3 to 80.6), attitudes (from 60.1 to 82.5), and actions (from 52.7 to 78.9) with a p-value <0.05. These findings indicate that outreach plays an important role in shaping community preparedness for disasters. Therefore, the implementation of sustainable education programs in disaster-prone areas is needed to increase community capacity in facing emergency situations